Manajemen Produksi Menggunakan Pendekatan 6M pada PT Ciomas Adisatwa Unit Pemalang - Ikhwan, Muh; Agustina, Yohana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
ABSTRACT Production management is an important element in the company's operations to ensure that products are produced in accordance with the specifications of customer demand, in the face of global competition, PT Ciomas Adisatwa Unit Pemalang is required to implement innovative and sustainable production strategies. This study aims to analyze the implementation of production management at PT Ciomas Adisatwa Unit Pemalang with the approach of 6M Men (Human Resources), Machinery, (Machinery and Technology), Materials, Methods (Production Methods), Markets, and Money (Capital and Finance). This study uses a descriptive qualitative method with purposive sampling technique. Data was collected through interviews, observations, and documentation, the number of respondents in this study was 10 people. The results of the study show that PT Ciomas Adisatwa Unit Pemalang implements a professional labor recruitment system, strict selection of raw material suppliers, production methods based on GMP and SOPs guided by the FSSC 22000 V6 food safety scheme, marketing strategies with a marketing mix method, and from a financial perspective, capital management is carried out in a structured manner to support business sustainability.